PERENCANAAN DINDING PENAHAN PASANGAN BATU KALI PADA SUNGAI CELAKET DESA GADING KULON KECAMATAN DAU KABUPATEN MALANG - Suhudi Suhudi; Kiki Frida Sulistiani; Andreas Andreas (Universitas Tribhuwana Tunggadewi Malang, 2017)
Problems landslides are common in Indonesia , especially during the rainy season which resulted in an increase in the volume of water, soil conditions become unstable, this often creates victims of both fatalities and casualties material. One of the locations with frequent landslides in Residence of Malang. One of the ways used to control stability of the land so as not to slide is to build a retaining wall. Planning retaining wall is located on the River Celaket, Gading Kulon village, subdistrict Dau, Malang. In this plan, the data is taken directly through laboratory tests in soil mechanics laboratory civil engineering Tribhuwana Tunggadewi Malang University. The type of planned retaining wall is gravity type. In order to the building can be function properly, then the stability of the building must also be planned as best as possible, therefore, The stability of the retaining wall analyzed to the danger of rolling (bolting) and sliding in normal water conditions without the earthquake, dwite the earthquake and flood water level conditions without the earthquake, with earthquakes Analyzed using the Rankine formula. The result is SFsliding 1,81 1,5 dan 1,32 1,2, SFbolters 2,07 1,5 dan 1,36 1,2 (for normal conditions without and with earthquake) dan SFsliding 2,11 1,5 and 1,49 1,2 SFbolters 2,10 1,5 dan 1,26 1,2 (for flood condition without and with earthquake), it turns out safely. This study also included with the method of exercising the work used a system of mutual assistance or nongovernmental and calculate the budget plan, which totals Rp.340.503.000